Use of Ceramic and Brick Decorations in Cultural Heritage Objects in Samarkand (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article describes the use of natural stone in the cladding of buildings new to the period in question, along with clay ceramics and faience products, in which the stone surface is marked with girih patterns, cut along these pattern lines and treated with ribbon-shaped glazed ceramics.